0340 Non-Surgical Maxillary Expansion Using A Novel Oral Appliance System. (25th May 2022) - Heckman, Seth; Katz, Daniel; Kushida, Clete
Abstract: Introduction: Complete Airway Repositioning and Expansion (CARE; Vivos Therapeutics, USA) consists of a series of dental devices that cause gradual expansion of the airway over an 18-month course used to treat mild-to-moderate obstructive sleep apnea. In this retrospective database review we sought to determine whether airway and obstructive sleep apnea (OSA) parameters changed via treatment as measured without the appliance in their mouths. Methods: After IRB exemption by the Mount Sinai Health System IRB (STUDY-21-01561) we conducted a retrospective review of the Vivos database. Demographics, pre-, mid-, or post-treatment maxillary dimensions, and pre-, mid-, or post- treatment sleep study parameters were reviewed. CBCT parameters for trans-palatal width (TPW) and total three dimensional (3D) airway volume were analyzed along with available AHI data. Results: There were 786 patients with complete radiographic datasets. The median (interquartile range) age was 49 (36-59) years, and half were female. Both the median TPW of 33.5 (31.0-35.3) mm and median 3D volume of 19, 752 (15965-25042) mm3 increased, to 35.0(33.0-37.5) mm and 21919 (17484-27711) mm3, respectively. These increases were significantly different (p<0.001 in both measures by related-samples Wilcoxon signed rank test). A subset of patients had complete sleep study data (N=139). For those patients with pre- and post-treatment studies who had also completed at least 18 months of therapy (N=37), the TPW increased by a median of 2.50 (1.00-3.50) mm and the 3D volume by a median of 3092 (1006-6480) mm3. Overall, the number of patients with no OSA went from 4 to 13 and the number of patients with severe OSA went from 10 to 3. Twenty-five patients (65%) had improved AHI, and 15 (41%) had their AHI improve by 50% or more (all of these were decreased to an AHI <20). Conclusion: This retrospective database review showed that OSA patients treated with BOAT improved their OSA with concomitant increases in maxillary dimensions. Further analyses of these data, and future prospective clinical trials are warranted to better understand this novel OSA treatment. Support (If Any): Support from Vivos Therapeutics in the form of granting access to their database and compensated clinical advisors.